The Role of Islamic Bank in Optimizing Zakat in Aceh - Asra, Asra; Syahputra, Angga (LAA MAISYIR : Jurnal Ekonomi Islam, 2021)
The existence of Islamic Finance in almost the whole areas of Aceh should result in prosperity to the people of Aceh (Acehnese). However, things occurred in the actual condition is completely the opposite, which according to the data, it shows that Aceh became the poorest province on the island of Sumatra in 2020. This study employed qualitative data concerning on discovering the role of Islamic banks in optimizing zakat in Aceh. The data was conducted under the form of literature review. The data sources used were secondary data through existing literatures, previous researches, and other relevant data. The results of the study indicate that Islamic banks have a significant role in optimizing zakat in Aceh. This covers the role of the Islamic bank as a central intermediary among various parties and their performances piloted by the resources they have. These roles include building interconnections between Islamic social finance and Islamic commercial finance, promoting and developing applications of Islamic principles through CSR funds, collaborating with various LAZs by utilizing existing banking facilities to collect zakat funds and increasing zakat literacy to customers.